2020
DOI: 10.1038/s41598-020-62146-0
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty with a Ti6Al4V/PEEK Prosthesis on an Osteoarthritis Rat Model: Behavioral and Neurophysiological Analysis

Abstract: Arthroplasty is a surgical procedure to restore the function of the joint of patient suffering from knee osteoarthritis. However, postoperative functional deficits are reported even after a rehabilitation program. In order to determine the origin of functional deficits of patient suffering from knee osteoarthritis and total knee arthroplasty, we developed a rodent model including a chemicallyinduced-osteoarthritis and designed a knee prosthesis (Ti6Al4V/PEEK) biomechanically and anatomically adapted to rat kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…When decalcification was achieved, samples were washed in deionized water, dehydrated in alcohol baths of increasing concentration ( , , , ), and finally cleaned with tissue clearing agent (Histo-Clear-II, National diagnostics, Atlanta, USA). Knee joints were infiltrated in three successive baths of liquid paraffin during 4 h and embedded in paraffin (polyisobutylene mixture, Paraplast plus, Sigma-Aldrich) 23 .
Figure 4 Sample decalcification during histological protocol monitored by X-ray imaging.
…”
Section: Methodsmentioning
confidence: 99%
“…When decalcification was achieved, samples were washed in deionized water, dehydrated in alcohol baths of increasing concentration ( , , , ), and finally cleaned with tissue clearing agent (Histo-Clear-II, National diagnostics, Atlanta, USA). Knee joints were infiltrated in three successive baths of liquid paraffin during 4 h and embedded in paraffin (polyisobutylene mixture, Paraplast plus, Sigma-Aldrich) 23 .
Figure 4 Sample decalcification during histological protocol monitored by X-ray imaging.
…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the ratio of weight-bearing distribution calculated as left/right hind paw, as previously reported. 18 Stimulus-evoked responses, such as the von Frey test, have been widely used in pain research to assess pain-related behavior. However, we selected DWB in this study because asymmetric weight distribution partially reflects spontaneous pain during free walking in unilateral paw pain models, [25][26][27] which appears to be more relevant and clinically important for assessing our novel JR model.…”
Section: Postoperative Assessments Behavioral Assessmentsmentioning
confidence: 99%
“…13,14 To develop a more effective treatment strategy, it is essential to clarify the basic mechanisms underlying postsurgical pain in the acute phase. There have been some reports of animal models exhibiting JR, [8][9][10][16][17][18] but the authors have made no mention of postsurgical pain. Among them, very few studies [16][17][18] reported on the JR model using rodents, which have been most extensively used for pain research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidation of such pathways necessitates a preclinical TKA model that closely mimics the clinical procedure as well as outcomes including acute postoperative pain and recovery of function. While several TKA models have been reported in rats [14][15][16][17], none of these have demonstrated responsiveness to analgesia and complete restoration of knee function as reported in clinical studies. Herein, we describe a new preclinical model of TKA in rats that is accompanied by behaviors indicative of acute postoperative pain responsive to clinically employed analgesics, and exhibits functional recovery and pain resolution as observed in TKA patients.…”
Section: Introductionmentioning
confidence: 99%